Results of the phase I open label clinical trial SAKK 06/14 assessing safety of intravesical instillation of VPM1002BC, a recombinant mycobacterium Bacillus Calmette Guérin (BCG), in patients with non-muscle invasive bladder cancer and previous failure of conventional BCG therapy. (1st January 2020) - Rentsch, Cyrill A.; Bosshard, Piet; Mayor, Grégoire; Rieken, Malte; Püschel, Heike; Wirth, Grégory; Cathomas, Richard; Parzmair, Gerald P.; Grode, Leander; Eisele, Bernd; Sharma, Hitt; Gupta, Manish; et al.
ABSTRACT: Background : VPM1002BC is a modified mycobacterium Bacillus Calmette Guérin (BCG) for the treatment of non-muscle invasive bladder cancer (NMIBC). The genetic modifications are expected to result in better immunogenicity and less side effects. We report on patient safety and immunology of the first intravesical application of VPM1002BC in human. Methods : Six patients with BCG failure received a treatment of 6 weekly instillations with VPM1002BC. Patients were monitored for adverse events (AE), excretion of VPM1002BC and cytokines, respectively. Results : No DLT (dose limiting toxicity) occurred during the DLT-period. No grade ≥3 AEs occurred. Excretion of VPM1002BC in the urine was limited to less than 24 hours. Plasma levels of TNFα significantly increased after treatment and blood-derived CD4+ T cells stimulated with PPD demonstrated significantly increased intracellular GM-CSF and IFN expression. Conclusion : The intravesical application of VPM1002BC is safe and well tolerated by patients and results in a potential Th1 weighted immune response.